2019
DOI: 10.1002/ctpp.201800136
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetic field on plasma particles in dusty plasma

Abstract: In this work, we present the investigation of the formation features and internal structure of dust clouds created in plasma of glow discharge in the external magnetic field corresponding to a range of moderate and strong fields, at which the ion component is magnetized. The analysis of the plasma magnetization in the presence of dust components is carried out. We defined the values of magnetic induction at which the changes in dynamics of plasma particles in magnetic field in light inert gases are expected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Further, it is observed that, even at relatively low magnetic fields (where still h i < 1 ), ensembles of trapped dust particles rotate as a whole around the magnetic field axis, see e.g. (Nunomura et al 1997;Sato et al 2001;Cheung et al 2003;Carstensen et al 2009;Karasev et al 2006Karasev et al , 2019. The rotation direction usually is in the r × direction where r is the (horizontal, radial, perpendicular) electric field that confines the dust particles transverse to the magnetic field.…”
Section: Rotationmentioning
confidence: 99%
“…Further, it is observed that, even at relatively low magnetic fields (where still h i < 1 ), ensembles of trapped dust particles rotate as a whole around the magnetic field axis, see e.g. (Nunomura et al 1997;Sato et al 2001;Cheung et al 2003;Carstensen et al 2009;Karasev et al 2006Karasev et al , 2019. The rotation direction usually is in the r × direction where r is the (horizontal, radial, perpendicular) electric field that confines the dust particles transverse to the magnetic field.…”
Section: Rotationmentioning
confidence: 99%
“…Figure 7 shows that both the positive and negative peaks become trapped, they neither propagate or dissolve by diffusion in the system over the time scale of the simulation. This behavior is the consequence of the well known scenario that diffusion can be strongly blocked by a magnetic field in strongly coupled plasmas [47,[68][69][70][71]. In the trapped state the particles undergo a cyclotron-type motion characterized by the strength of the magnetic field (β).…”
Section: B the Effect Of The Magnetic Fieldmentioning
confidence: 99%
“…While air pressure induction discharges weren't identified until the 1940s, low-pressure electrodeless discharge experiments began around the end of the 19th century [1][2][3]. Ring releases, once established at low pressure, could be sustained when the pressure increased to atmospheric pressure, according to Babat's 1947 paper [4][5]. As far as we know, inductively linked plasma discharges may be maintained in open tubes with airflow [6][7].…”
Section: Introductionmentioning
confidence: 99%